2012
DOI: 10.1097/aln.0b013e3182700901
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Respiratory Variations in Pulse Oximetry Plethysmographic Waveform Amplitude and Arterial Pulse Pressure during Major Abdominal Surgery

Abstract: The wide limits of agreement between ΔPP and ΔPOP and the weak correlation between both values cast doubt regarding the ability of ΔPOP to substitute ΔPP to follow trend in preload dependence and classify respiratory cycles as responders or nonresponders using standard monitor during anesthesia for major abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
1
26
3
Order By: Relevance
“…Future research to design algorithms incurring less delay could further aid the clinical utility of PPG-derived PAV as a non-invasive measure of PPV. The original agreement between finger-derived PAV and ABP-derived PPV found in this work (3.2 ± 5.1%) was better than that reported by Hengy et al [13] (5.2 ± 8.4%). This may be attributed to be the fact that PPV values changed marginally for some patients in our dataset.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Future research to design algorithms incurring less delay could further aid the clinical utility of PPG-derived PAV as a non-invasive measure of PPV. The original agreement between finger-derived PAV and ABP-derived PPV found in this work (3.2 ± 5.1%) was better than that reported by Hengy et al [13] (5.2 ± 8.4%). This may be attributed to be the fact that PPV values changed marginally for some patients in our dataset.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition to BV, we also studied the influence of the PPV, the ratio of the respiration rate and the heart rate, and perfusion index on the agreement between PPV and PAV, as these were found or assumed to have an impact in previous work [13,14,20]. In this work, PI was calculated as ratio between the pulsatile (AC) component and the slowlychanging (DC) component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[82][83][84][85] Despite the growing body of data suggesting that PVI is capable of predicting fluid responsiveness, there does not seem to be strong agreement between PVI and PPV. [86][87][88][89][90] The reasons for this paradox (excellent predictor of fluid responsiveness yet not in agreement with arterial-derived metrics) are not clear but may be related to the dependence of PVI on perfusion. 91 While the Masimo device may not be as effective as its more invasive counterparts during periods of malperfusion, it has three major advantages -relative low cost in comparison with its competitors, the ubiquity of pulse oximetry (which of course is a Canadian Anesthesiologists' Society basic monitoring standard), 92 and ease of use.…”
Section: Technological Assessmentmentioning
confidence: 99%
“…While some studies have shown a meaningful correlation between the two, 52,53 the majority of studies comparing arterial and PPG respiratory variation point to a relatively weak correlation. [54][55][56][57][58] Solus-Biguenet et al, for instance, found a weak correlation of 0.29. 54 Nevertheless, despite this weak correlation, the majority of fluid responsiveness studies suggest that the respiratory variation in the PPG tracing is predictive of the hemodynamic response to fluid loading, [59][60][61][62][63] although this finding is not universal.…”
Section: Fluid Responsivenessmentioning
confidence: 99%